Cardioprotective effect of paeonol against epirubicin-induced heart injury via regulating miR-1 and PI3K/AKT pathway. (25th April 2018) - Wu, Jing; Sun, Chao; Wang, Ruoyi; Li, Juan; Zhou, Meng; Yan, Mi; Xue, Xia; Wang, Chuanxin
Abstract: Cardiotoxicity is a dose-dependent side effect of epirubicin that restricts its clinical utility in cancer chemotherapy. Paeonol is an active constituent with various biological activities, including the protection of antineoplastic-induced toxicities. In the present study, we investigated the protective effect of paeonol on epirubicin-induced cardiotoxicity and explored the underlying mechanism. A series of methods were used including a MTT assay, flow cytometry, echocardiography, TUNEL staining, a dual-luciferase reporter assay, immunofluorescence, RT-PCR and Western blotting. The results indicate that paeonol improves cardiac dysfunction, relieves histopathological changes, alleviates inflammation, reduces myocardial apoptosis and increases autophagy. Further studies suggest that paeonol upregulates the decreased expression of miR-1 caused by epirubicin and thus inhibits the activation of PI3K/AKT/mTOR and NF-κB pathways. In conclusion, paeonol effectively ameliorates myocardial injury by increasing miR-1 expression to suppress the PI3K/AKT/mTOR and NF-kB signalling pathways. Graphical abstract: The possible mechanism of protective effect of paeonol on epirubicin-induced cardiotoxicity.The repressed autophagy induced by epirubicin was involved in myocardial apoptosis and that paeonol, a potential myocardial protective drug, effectively ameliorated myocardial injury by reinforcing slight autophagy. This occurred through increased miR-1 expression to suppress the PI3K/AKT/mTOR and NF-κB signalling pathways. Highlights: Paeonol effectively meliorates the myocardial injury induced by Epirubicin in vitro and in vivo. Paeonol promotes miR-1 expression and up-regulates autophagy in epirubicin-induced cardiotoxicity. Paeonol inhibites PI3K/AKT/mTOR and NF-κB signalling pathways in epirubicin-induced cardiotoxicity.